UMA NOVA ESPÃ‰CIE DE ð˜‹ð˜ºð˜´ð˜°ð˜¯ð˜ªð˜¢ (ð˜›ð˜¦ð˜µð˜µð˜ªð˜¨ð˜°ð˜¯ð˜ªð˜ªð˜¥ð˜¢ð˜¦, ð˜—ð˜©ð˜¢ð˜¯ð˜¦ð˜³ð˜°ð˜±ð˜µð˜¦ð˜³ð˜ªð˜¯ð˜¢ð˜¦) ENCONTRADA NO ESTADO DE MATO GROSSO - Piza Jr., S. de Toledo; Peres Filho, OtÃ¡vio (REVISTA DE AGRICULTURA, 2020)
UMA NOVA ESPÃ‰CIE DE ð˜‹ð˜ºð˜´ð˜°ð˜¯ð˜ªð˜¢ (ð˜›ð˜¦ð˜µð˜µð˜ªð˜¨ð˜°ð˜¯ð˜ªð˜ªð˜¥ð˜¢ð˜¦, ð˜—ð˜©ð˜¢ð˜¯ð˜¦ð˜³ð˜°ð˜±ð˜µð˜¦ð˜³ð˜ªð˜¯ð˜¢ð˜¦) ENCONTRADA NO ESTADO DE MATO GROSSO